2009
DOI: 10.1103/physrevlett.103.257003
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Iron Isotope Effect on the Transition Temperature of the(Ba,K)Fe2As2Superconductor

Abstract: Abstract:We report that (Ba,K)Fe 2 As 2 superconductor (a transition temperature, T c ~ 38 K) has inverse iron isotope coefficient α Fe = -0.18(3) (where T c ~ M -αFe and M is the iron isotope mass), i.e. the sample containing the larger iron isotope mass depicts higher T c . Systematic inverse shifts in T c were clearly observed between the samples using three types of Fe-isotopes ( Polycrystalline samples of (Ba,K)Fe 2 As 2 were prepared by high-pressure synthesis method [14]. The sample synthesized from a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
91
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 30 publications
3
91
1
1
Order By: Relevance
“…As such, the independent on T c value of α int Fe would suggest α str Fe ∼ −0.4 for SmFeAsO 1−x studied by Shirage et al 17 To conclude, the currently available Fe isotope effect data on the superconducting transition temperature T c for various Fe-based HTS were reanalyzed by separating the measured Fe-IE exponent α Fe into a structural and an intrinsic (unrelated to the structural changes) component. Accounting for the empirical relation between T c and the anion atom height h An 21 we have demonstrated that the structural contribution to the Fe-IE exponent is negative for Ba 0.6 K 0.4 Fe 2 As 2 and SmFeAsO 1−x studied by Shirage et al, 16,17 positive for FeSe 1−x , 18 and close to 0 for SmFeAsO 0.85 F 0.15 and Ba 0.6 K 0.4 Fe 2 As 2 measured by Liu et al 15 By taking such corrections into account we infer that the value of the genuine Fe-IE exponent is close to α int Fe ∼ 0.35 − 0.4 for compounds belonging to at least three different families of Fe-based HTS. We are convinced that the analysis presented in our paper helps in clarifying the existing controversy on the isotope effect in Fe-based superconductors.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…As such, the independent on T c value of α int Fe would suggest α str Fe ∼ −0.4 for SmFeAsO 1−x studied by Shirage et al 17 To conclude, the currently available Fe isotope effect data on the superconducting transition temperature T c for various Fe-based HTS were reanalyzed by separating the measured Fe-IE exponent α Fe into a structural and an intrinsic (unrelated to the structural changes) component. Accounting for the empirical relation between T c and the anion atom height h An 21 we have demonstrated that the structural contribution to the Fe-IE exponent is negative for Ba 0.6 K 0.4 Fe 2 As 2 and SmFeAsO 1−x studied by Shirage et al, 16,17 positive for FeSe 1−x , 18 and close to 0 for SmFeAsO 0.85 F 0.15 and Ba 0.6 K 0.4 Fe 2 As 2 measured by Liu et al 15 By taking such corrections into account we infer that the value of the genuine Fe-IE exponent is close to α int Fe ∼ 0.35 − 0.4 for compounds belonging to at least three different families of Fe-based HTS. We are convinced that the analysis presented in our paper helps in clarifying the existing controversy on the isotope effect in Fe-based superconductors.…”
mentioning
confidence: 78%
“…However, a zero, within the experimental accuracy, Fe isotope shift of the c-axis lattice constant for Ba 0.6 K 0.4 Fe 2 As 2 as reported by Liu et al 15 is a clear indication that no structural effect is present for this particular set of the samples. Consequently, the negative isotope effect exponent α Fe ≃ −0.18 obtained for nominally identically doped Ba 0.6 K 0.4 Fe 2 As 2 by Shirage et al 16 stems from summing both effects, i.e., −0.18(α Fe ) = 0.35(α int Fe ) − 0.52(α str Fe ), see Eq.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…The phase-difference mode would yield new phenomena [6][7][8][9][10] and new excitation modes in multi-gapped superconductors. The negative isotope effect in Fe pnictides is an example of the multi-band effect [11,12]. The existence of fractionally quantized flux vortices is very significant and attractive.…”
Section: Introductionmentioning
confidence: 99%